Untangling the structural and molecular mechanisms underlying colour and rapid colour change in a lizard, Agama atra. Issue 10 (13th April 2021) - Nicolaï, Michaël P. J.; D'Alba, Liliana; Goldenberg, Jonathan; Gansemans, Yannick; Van Nieuwerburgh, Filip; Clusella‐Trullas, Susana; Shawkey, Matthew D.
Abstract: With functions as diverse as communication, protection and thermoregulation, coloration is one of the most important traits in lizards. The ability to change colour as a function of varying social and environmental conditions is thus an important innovation. While colour change is present in animals ranging from squids, to fish and reptiles, not much is known about the mechanisms behind it. Traditionally, colour change was attributed to migration of pigments, in particular melanin. More recent work has shown that the changes in nanostructural configuration inside iridophores are able to produce a wide palette of colours. However, the genetic mechanisms underlying colour, and colour change in particular, remain unstudied. Here we use a combination of transcriptomic and microscopic data to show that melanin, iridophores and pteridines are the main colour‐producing mechanisms in Agama atra, and provide molecular and structural data suggesting that rapid colour change is achieved via melanin dispersal in combination with iridophore organization. This work demonstrates the power of combining genotypic (gene expression) and phenotypic (microscopy) information for addressing physiological questions, providing a basis for future studies of colour change.